ELancing Motivation on Sribulancer, an Evidence from Indonesia - Ani Wulandari; Talisa Qamara; Salem Abdulaziz Mohammed Bawazir (Journal of World Conference (JWC), 2019)
eLancing is a growing trend in Indonesia. More and more people opt to become eLancers due to the job and time flexibility. This paper aims to explore further the motivational factors for Indonesian eLancers to work in Sribulancer, an online platform for freelancers. Using qualitative approach, 200 semi structured interviews were conducted to eLancers in Sribulancer.com. The result exhibited eight (8) primary motivations of eLancing such as work-family balance, flexibility and autonomy, economic incentives, skills development, trust and transparency,unemployment,passion and satisfaction, networking